Penilaian Pengetahuan Tertulis Dalam Kurikulum 2013 - Nurul Waizah; Herwani Herwani (Pascasarjana Pendidikan Agama Islam Institut KH. Abdul Chalim Mojokerto, 2021)
This assessment is needed to measure whether students have succeeded in achieving competence or not; information on learning outcomes is needed. Information on learning outcomes is obtained from bills that students must meet. Each type of bill requires a set of measuring tools or assessment tools. Here, the teacher's role is needed to make measuring tools and gather information on learning outcomes appropriately. They measure tools or assessment tools that can produce valid and reliable measurement results. Assessment of knowledge or cognitive competence is an assessment carried out by teachers to measure students' achievement or mastery in aspects of knowledge, including memory or memorization, understanding, application or application, analysis, synthesis, and evaluation. The 2013 curriculum is a philosophical foundation that develops all the potential of students to become quality human beings.